Lost and found: the late discovery of a migrated intrauterine device after 15 years - a case report - Saeed, Majed; Hassan, Naveed Ul; Nisar, Javeria; Afzal, Shahzad (International Surgery Journal, 2024)
Intrauterine devices (IUDs) are a preferred reversible contraceptive choice for about 159 million women worldwide. While generally safe, they pose risks like uterine perforation and device migration, which happen in about 1 in 1000 insertions. Other common issues include insertion failure, pain, infection, and menstrual changes. This report details a rare case of IUD migration in a 40-year-old woman, discussing the diagnostic challenges and the approaches used to manage such complications. IUD migration to the bladder is uncommon but can lead to serious, often undetected issues, thus underscoring the necessity for regular follow-up after placement. Early diagnosis with imaging is critical for proper treatment, with the World Health Organization recommending surgical removal in symptom-free cases. The rarity of uterine perforation during IUD use highlights the vital need for vigilant monitoring and patient follow-ups to prevent and quickly address such complications. The uncertain timing and cause of IUD migration further stress the importance of comprehensive counseling and regular patient check-ups. Abdominal discomfort may indicate an IUD has migrated, emphasizing the need for patient awareness and routine self-monitoring after placement. CT imaging is crucial for identifying and pinpointing the location of migrated IUDs, facilitating their removal using minimally invasive methods like colonoscopy and laparoscopy. For more complicated scenarios, such as those involving deep embedment, laparotomy may be necessary.